Transmission of Liquidity Shocks Evidence From the 2007 Subprime Crisis - Hesse, Heiko (International Monetary Fund, 2008)
We examine the linkages between market and funding liquidity pressures, as well as their interaction with solvency issues surrounding key financial institutions during the 2007 subprime crisis. A multivariate GARCH model is estimated in order to test for the transmission of liquidity shocks across U.S. financial markets. It is found that the interaction between market and funding illiquidity increases sharply during the recent period of financial turbulence, and that bank solvency becomes important
Includes bibliographical references
Keywords: Credit -- United States -- Econometric models; Financial crises -- United States; Liquidity (Economics) -- Econometric models; Subprime mortgage loans -- United States -- Econometric models; Electronic books